2021
DOI: 10.3389/fpubh.2020.584408
|View full text |Cite
|
Sign up to set email alerts
|

Managing Multimorbidity (Multiple Chronic Diseases) Amid COVID-19 Pandemic: A Community Based Study From Odisha, India

Abstract: While most of the studies to date demonstrate the deleterious effect of multiple chronic diseases on COVID-19 risk and outcome, there is sparse information available on the effect of the pandemic on multimorbidity management, with no reports yet from India. We sought to explore the effect of COVID-19 pandemic on routine and emergency care for multimorbidity among community-dwelling adults in Odisha, India. A community-based cross-sectional study was undertaken pandemic lockdown, in Khurda district of Odisha, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 40 publications
4
49
0
3
Order By: Relevance
“…Similar findings have been observed in a chart review of the morbidity profile of urban primary care patients 29 . Studies have documented the challenges in care-seeking for chronic illnesses like cancer and rheumatoid arthritis 32 33 34 35 . During pandemic situations, these challenges become accentuated due to the prevailing conditions and patient safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been observed in a chart review of the morbidity profile of urban primary care patients 29 . Studies have documented the challenges in care-seeking for chronic illnesses like cancer and rheumatoid arthritis 32 33 34 35 . During pandemic situations, these challenges become accentuated due to the prevailing conditions and patient safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Belgium, primary care providers observed disruption in the delivery of chronic care for conditions like diabetes and hypertension during the COVID-19 pandemic [ 8 ]. Individuals with multimorbidity (43%) reported more challenges compared to those with single condition (35%) [ 9 ]. The most challenging issue was physician consultation followed by diagnostic investigations (26%).…”
Section: Introductionmentioning
confidence: 99%
“…The most challenging issue was physician consultation followed by diagnostic investigations (26%). Transport logistics (33%), financial arrangements (26%), mobility-restrictions (21%), and fear of going to hospital owing to the risk of contagion (18%) were other prominent reported factors [ 9 ]. There was evidence of fall in screening tests for diabetes and dyslipidemia during months of February, March 2020 with modest rebound in early April 2020 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our own study has found the prevalence to be around 1/3rd in primary care patient population (Pati et al, 2015b). There is even significant multimorbidity among patients attending secondary and higher levels of health care, as well as specialized settings like psychiatry or antenatal clinics (Pati et al, 2021a;Pati et al, 2021b).…”
Section: Introductionmentioning
confidence: 90%